The Chinese text and context of the Russian literature - Kondakov, Boris; Wang, Kewen; Krasnoyarova (Popkova), Anna (Opción, 2019)
The article considers the emergence and development of the Chinese text as a distinctive phenomenon of Russian literature. For this purpose, the method of historicism was applied that allowed to consider the development of the Chinese culture in chronological order. Besides, the comparison method was used in relation to the Russian writers, Russian-Chinese literary works and various literary movements in Russia. As a result, it was shown that the Chinese text attracted the Russian writers with its simplicity and elegance, whereas the Chinese works influenced the formation of the Russian spiritual-philosophic thinking.